ANALISIS PENGARUH TINGKAT INFLASI, NILAI TUKAR, BI-RATE DAN SUKU BUNGA BANK KONVENSIONAL TERHADAP MARGIN BAGI HASIL DEPOSITO MUḌARABAH PERBANKAN SYARIAH DI INDONESIA PERIODE 2010-2015 - Faisal Affandi (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2016)
This research aims to analyze the effect level of inflation, exchange rate, BI-Rate and the bank conventional interest rate to the margin profit sharing of muḍarabah deposits the Islamic banking in Indonesia period January 2010 - December 2015. The data used  are time series data period January 2010 - December 2015 published by BI, OJK and BPS. The method of analysis used in this research is Multiple Linier Regression Method is Ordinary Least Square (OLS).The results of this research indicate that the level of inflation variable and the bank conventional interest rate variable partially no significant effect to the margin profit sharing of muḍarabah deposits the Islamic banking in Indonesia period 2010 - 2015 variable. While the exchange rate variable and the BI-Rate variable partially significant effect to the margin profit sharing of muḍarabah deposits the Islamic banking in Indonesia period 2010 - 2015 variable. The results of statistic test showed that together (simultaneously), the level of inflation variable, the exchange rate variable, the BI-Rate variable, and the bank conventional interest rate variable simultaneously significant effect to the margin profit sharing of muḍarabah deposits the Islamic banking in Indonesia period 2010 - 2015 variable.